Multifunctional PLGA nanosystems: enabling integrated diagnostic and therapeutic strategies - Li, Yue; Tao, Tao; Xiong, Yao; Guo, Weiyu; Liang, Yangbiao (Frontiers in Pharmacology, 2025)
In the past decades, biodegradable polymers have been widely used in pharmaceutical and medical engineering materials. Poly (lactic-co-glycolic acid) (PLGA) copolymer, renowned for its exceptional biocompatibility, inherent non-toxicity, and superior encapsulation and film-forming capabilities, has been widely acknowledged as one of the foremost candidate materials among next-generation biodegradable polymers with remarkable application potential. PLGA nanoparticles exhibit demonstrated versatility in accommodating hydrophobic or hydrophilic substances, which can be either encapsulated within their core matrix or adsorbed onto the surface. This includes chemical drugs, nucleic acids, peptides, and proteins. Upon entering the systemic circulation, the size-tunable characteristics of PLGA nanoparticles synergize with surface ligand-receptor interactions to confer dual-targeting capabilities: passive targeting through enhanced permeability and retention (EPR) effects, and active targeting via specific molecular recognition at pathological sites. Moreover, the integration of multimodal imaging capabilities into PLGA-based nanoparticles enables in vivo imaging-guided drug delivery, which paves the way for more precise and enhanced approaches to disease diagnosis and therapeutic intervention. This review systematically examines the fabrication strategies, structural variants of PLGA-based nanostructures, and their applications in both diagnostic and therapeutic domains of biomedicine.